1994
DOI: 10.1002/pola.1994.080320709
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of polymerization of 1‐octene with Mgcl2‐supported Ticl4 catalysts

Abstract: A number of TiCl4 catalysts supported on MgCl2 which was activated by the recrystallization method using different alcohols were prepared with ethyl benzoate or dibutyl phthalate as the internal electron donor. All the catalysts were characterized by BET, x‐ray diffraction, and hydrolysis–GC analysis. Kinetics of polymerization of 1‐octene was studied with three of the above catalysts (having different internal electron donors) activated by AlEt3. The rate of polymerization increased linearly with increasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…[1,2,18,21] The polymerization activity increased with increasing monomer concentration. It may be a result of higher access of active catalyst centers to the monomers that leads to increase of propagation rate compared with the chain transfer and deactivation reactions.…”
Section: Effect Of Monomer Concentrationmentioning
confidence: 98%
See 1 more Smart Citation
“…[1,2,18,21] The polymerization activity increased with increasing monomer concentration. It may be a result of higher access of active catalyst centers to the monomers that leads to increase of propagation rate compared with the chain transfer and deactivation reactions.…”
Section: Effect Of Monomer Concentrationmentioning
confidence: 98%
“…Kothandaraman et al also reported a linear relationship between the increasing rate of 1-octene polymerization with increasing monomer concentrations. [18] It was expected that the M v of the poly (1-hexene) would also increase with increasing monomer concentration, evidence that chain transfer to 1-hexene was not important. [21] Poly (1-hexene) with the highest M v (2.7 × 10 3 kDa) was obtained in the slurry phase using 0.3 mol of monomer (Fig.…”
Section: Effect Of Monomer Concentrationmentioning
confidence: 99%
“…This effect is characteristic of homogeneous [21][22][23] catalyst systems, which has been attributed to the decrease in the concentration of active centers present in the catalyst systems. 13,24 Effect of aging time…”
Section: Effect Of Reaction Timementioning
confidence: 99%
“…Despite the considerable amount of mechanistic details available for the polymerization kinetics of higher and branched ␣-olefins with heterogeneous catalyst systems, less is known with soluble, homogenous catalyst systems, specifically when the halogen atoms in the transition metal salts are replaced with organic groups or complex organic ligands. 3,13 Thus, to shed some light on the efficiency of soluble, homogenous Ziegler-Natta-type catalytic systems and also to observe for the monomer isomerization polymerization with the selected catalyst system, we carried out in the present work a systematic kinetic study on the polymerization of 4-methylpentene-1 (4MP1), a liquid monomer which is thermodynamically the most unstable propylene dimer of the methyl pentenes, in benzene medium by using acetyl aceto-nates of various transition metals (viz., Cr, Mn, Fe, and Co) with triethyl aluminum as cocatalyst.…”
mentioning
confidence: 99%
“…They have shown that donor type has dominant effect on the polymerization kinetic as well as isotacticity pentad. [10] The microstructure of PB and PP, synthesized with MgCl 2 /TiCl 4 (2.00 wt%) catalytic system containing | 2589 SHIRBAKHT eT Al. triethoxyphenylsilane and tetramethylpiperidine as external donors, was studied by Busico et al [11] They found out that in highly isotactic polymers, the percentage of mmmm in PB and PP are 78% and 90%, respectively.…”
Section: Introductionmentioning
confidence: 99%